An In Vitro Anticancer Activity Evaluation of Neolamarckia cadamba (Roxb.) Bosser Leaves’ Extract and its Metabolite Profile - Razali, Shakirah; Firus Khan, Al’aina Yuhainis; Khatib, Alfi; Ahmed, Qamar Uddin; Abdul Wahab, Ridhwan; Zakaria, Zainul Amiruddin (Frontiers in Pharmacology, 2021)
Neolamarckia cadamba (NC) leaf is traditionally used for the treatment of breast cancer, however, this claim is unverified scientifically. This study aimed to evaluate the anti-cancer activities of NC leaf ethanol extract on breast cancer cell line (MCF-7 cells) using in vitro cell viability, cytotoxicity, and gene expression assays followed by gas chromatography analysis. Results revealed inhibition concentration (IC50) against MCF-7 at 0.2 mg/mL. The extract exerted a dose and time-dependent inhibitory effect against MCF-7 cells. The cell cycle assay showed that the extract arrested MCF-7 cells in the G0/G1 phase, and apoptosis was observed after 72 hours by Annexin-V assay. The gene expression assay revealed that the cell cycle arrest was associated with the down-regulation of CDK2 and subsequent up-regulation of p21 and cyclin E. The extract induced apoptosis via the mediation of the mitochondrial cell death pathways. Chromatography analysis revealed the contribution of D-pinitol and myo-inositol to the activity observed as the two major bioactive compounds. Overall, the study demonstrated that NC exerts anti-cancer effects on MCF-7 human breast cancer cells through induction of apoptosis and cell cycle arrest thus justifying its traditional use for the treatment of breast cancer in Malaysia.